Three in one dental mirror: inovation of oral diagnostic instrument - Irene E. Rieuwpassa; Andi M. Rizal; Ansyari Muis; Harun H. Lala (DiscoverSys Inc., 2019)
Objective: This invention is to facilitate the work of the dentist in terms of examination and treatment, and increase the efficiency of time and reduce the risk of nosocomial infection.Material and Methods: The tool that used to clean debris and water that covered the mirror surface is a dental syringe which can spray water and air. But the use of dental syringe will reduce treatment effectiveness and time efficiency, it can even increase the risk of nosocomial infection.Results: The optimal pressure for this instrument to prevent and to clean stains on the mirror surface is between 2.5-4 bar (1 bar =0.1 MPa).Conclusion: The multifunctional prototype of dental mirror which is a combination of three dental instruments in one tool has been created using the 3D printing method